Effects of irrigation frequency on root growth, nutrients accumulation, yield, and water use efficiency of Panax notoginseng under micro-sprinkler irrigation - Huang, Hui; Shi, Yuzhe; Luo, Anrong; Xiao, Yanan; Liang, Jiaping; He, Zijian (Frontiers in Plant Science, 2025)
Micro-sprinkler irrigation has been a promising irrigation method to promote Panax notoginseng (Burk) F. H. Chen production but their scientific irrigation frequency in improving yield and water use efficiency of P. notoginseng remains contradictory and inconclusive. The objective of this study was therefore to examine and propose a scientific irrigation frequency in water management of P. notoginseng cultivation considering their impact on soil water, soil available nutrients, root growth, yield, and water use efficiency (WUE). The micro-sprinkler irrigation experiment under shading and rain-shelter conditions was carried out in the growing season of P. notoginseng from 2017 to 2018.The treatments included four micro-sprinkler irrigation frequencies, such as IF1 (irrigation once every three days), IF2 (irrigation once every five days), IF3 (irrigation once every seven days), and IF4 (irrigation once every nine days) in 2017-2018. The results indicated that the IF3 treatment significantly increased the nitrogen accumulation of P. notoginseng (271.98 mg plant-1). In addition, the IF2 treatment enhanced the phosphorus accumulation (27.82 mg plant-1), potassium accumulation (408.38 mg plant-1), total root surface area (67.49 cm2 plant-1), total root volume (3.79 cm3 plant-1) and yield (702 kg ha-1). The IF2 treatment significantly increased WUE by 29.2%, 28.1%, and 37.7% compared with the IF1, IF3, and IF4 treatments, respectively. Our findings suggested that IF2 treatment increased the soil water content, reduced the soil nutrient content, increased the accumulation of phosphorus and potassium in P. notoginseng, promoted the root growth of P. notoginseng, and improved the quality and yield of P. notoginseng, providing a scientific theoretical basis for reasonable water control and green quality production in the cultivation of P. notoginseng under shade and rain shelter cultivation.